Development of a biomarker of efficacy in second-line treatment for lymphangioma of the tongue: a pilot study. Issue 10 (December 2019) - Pandey, V.; Tiwari, P.; Sharma, S.P.; Kumar, R.; Panigrahi, P.; Singh, O.P.; Patne, S.
Abstract: Lymphangioma of the tongue is a rare lymphatic malformation, and various authors have reported the successful use of sirolimus for its treatment. However, the safety of sirolimus in children needs further evaluation so that those who do not respond are not necessarily exposed to its potential adverse effects. We hypothesised that assessment of lymphangiogenesis can be used to predict whether the patient will respond to sirolimus, so we organised a prospective study after ethics committee approval had been given. After clinical and histological diagnoses of lymphangioma of the tongue had been confirmed, 16 patients were given sirolimus 0.8 mg/day in three divided doses. Clinical response was assessed and compared with lymphatic microvessel density (LMVD), which was calculated immunohistochemically using the monoclonal antibody D2-40 as the lymphatic endothelial marker. Nine patients responded well, five partially, and two failed to respond. Mean (SD) LVD among the good responders was 21.00 (3.74), whereas among non-responders it was 8.00 (4.24). There was a significant difference in mean LVD between good responders, partial responders, and non-responders (p = 0.04). Sirolimus is effective in treating children with lymphangioma of the tongue, and lymphangiogenesis is a useful therapeutic predictive marker.